Hölderlin, Subjektivität und Moderne (Studia theodisca, 2014)
Moving from Schiller’s rebuke about Hölderlin’s «wild subjectivity», the contribution briefly discusses this concept in a late 18th century context. Hölderlin’s poetry is then analyzed in the light of his modern understanding of subjectivity, with particular regard to the late hymns Remembrance and Mnemosyne.